Estudo da reidratação do feijão verde (Vigna unguiculata L. Walp) desidratado por micro-ondas com e sem pré-tratamento osmótico - Queiroga, Priscila Vanini Dantas de Medeiros (2012)
The green bean has organoleptic and nutritional characteristics that make it an important food source in tropical regions such as the Northeast of Brazil. It is a cheap source of protein and important for nutrition of rural population contributing significantly in subsistence farming of the families from Brazil s northeast. It is consumed in entire region and together with the dry meat and other products composes the menu of typical restaurants, being characterized as an important product for economy of Northeast. The green bean is consumed freshly harvested and has short cycle, being characterized as a very perishable food, which hampers your market. The drying method is an alternative to increase the lifetime and provide a reduction volume of this product making easier your transportation and storage. However is necessary to search ways of drying which keep the product quality not only from the nutritional standpoint but also organoleptic. Some characteristics may change with the drying process such as the coloring, the rehydration capacity and the grains cooking time. The decrease of drying time or of exposure of the grains to high temperature minimizes the effects related with the product quality loss. Among the techniques used to reduce the drying time and improve some characteristics of the product, stands out the osmotic dehydration, widely used in combined processes such as the pretreatment in drying food. Currently the use of the microwaves has been considered an alternative for drying food. The microwave energy generates heat inside of materials processed and the heating is practically instantaneous, resulting in shorter processing times and product quality higher to that obtained by conventional methods. Considering the importance of the green beans for the Northeast region, the wastefulness of production due to seasonality of the crop and your high perishability, the proposal of this thesis is the study of drying grain by microwaves with and without osmotic pretreatment, focusing on the search of conditions of processes which favor the rehydration of the product preserving your organoleptic characteristics. Based on the analysis of the results of osmotic dehydration and dielectric properties was defined the operating condition to be used in pretreatment of the green bean, with osmotic concentration in saline solution containing 12,5% of sodium chloride, at 40°C for 20 minutes. The drying of green bean by microwave was performed with and without osmotic pretreatment on the optimized condition. The osmotic predehydration favored the additional drying, reducing the process time. The rehydration of dehydrated green bean with and without osmotic pretreatment was accomplished in different temperature conditions and immersion time according to a factorial design 22, with 3 repetitions at the central point. According to results the better condition was obtained with the osmotically pretreated bean and rehydrated at a temperature of 60°C for 90 minutes. Sensory analysis was performed comparing the sample of the green bean in natura and rehydrated in optimized conditions, with and without osmotic pretreatment. All samples showed a good acceptance rate regarding the analyzed attributes (appearance, texture, color, odor and taste), with all values above 70%. Is possible conclude that the drying of green bean by microwave with osmotic pretreatment is feasible both in respect to technical aspects and rehydration rates and sensory quality of the product